Cross‐cultural evidence of value structures and priorities in childhood. (12th January 2015) - Döring, Anna K.; Schwartz, Shalom H.; Cieciuch, Jan; Groenen, Patrick J. F.; Glatzel, Valentina; Harasimczuk, Justyna; Janowicz, Nicole; Nyagolova, Maya; Scheefer, E. Rebecca; Allritz, Matthias; Milfont, Taciano L.; Bilsky, Wolfgang
<x xml:space="preserve">Abstract</x> We broaden the developmental focus of the theory of universals in basic human values (Schwartz, 1992, Advances in Experimental Social Psychology) by presenting supportive evidence on children's values from six countries: Germany, Italy, Poland, Bulgaria, the United States, and New Zealand. 3, 088 7–11‐year‐old children completed the Picture‐Based Value Survey for Children (PBVS‐C, Döring et al., 2010, J. Pers. Assess., 92, 439). Grade 5 children also completed the Portrait Values Questionnaire (PVQ, Schwartz, 2003, A proposal for measuring value orientations across nations. Chapter 7 in the Questionnaire Development Package of the European Social Survey). Findings reveal that the broad value structures, sex differences in value priorities and pan‐cultural value hierarchies typical of adults have already taken form at this early age. We discuss the conceptual implications of these findings for the new field of children's basic values by embedding them in the recent developmental literature.